Ultrasound‐MRI Correlation for Healing of Rotator Cuff Repairs Using Power Doppler, Sonographic Shear Wave Elastography and MR Signal Characteristics: A Pilot Study. (1st December 2020) - Nocera, Nicole L; Burke, Christopher J; Gyftopoulos, Soterios; Adler, Ronald S.
Abstract : Objective: To determine whether the healing response in rotator cuff repairs can be quantitatively characterized using a multimodality imaging approach with MR signal intensity, power Doppler and shear wave elastography (SWE). Materials and Methods: Patients scheduled for rotator cuff repair were prospectively enrolled between September 2013 and June 2016. A 12 patient cohort with unilateral, full‐thickness, supraspinatus tendon tears underwent MRI and ultrasound both preoperatively and postoperatively (at 3 and 6 months post‐surgery). The MR signal intensity ratio of tendon‐to‐deltoid muscle (TMR), vascularity score by power Doppler (PD) and shear wave velocity (SWV) were measured. Repaired and asymptomatic control shoulders were compared over time and between modalities. Results: TMR and vascularity of the tendon repair initially increased and then decreased postoperatively. Although not achieving statistical significance, postoperative SWV initially decreased and later increased, which negatively correlated with the TMR at 3 months (r = ‐0.73, p = 0.005). PD demonstrated a statistically significant change in tendon vascularity over time compared to the contralateral control (p = 0.009 at 3 months; p = 0.036 at 6 months). No significant correlation occurred between TMR and SWE at 6 months, or with PD at any time point. Conclusion: Despite a small patient cohort, this prospective pilot study suggests a temporal relationship of MRI and ultrasound parameters that parallels the expected phases of healing in the repaired rotator cuff.